2014
DOI: 10.1111/gcb.12522
|View full text |Cite
|
Sign up to set email alerts
|

Soil animal responses to moisture availability are largely scale, not ecosystem dependent: insight from a cross‐site study

Abstract: Climate change will result in reduced soil water availability in much of the world either due to changes in precipitation or increased temperature and evapotranspiration. How communities of mites and nematodes may respond to changes in moisture availability is not well known, yet these organisms play important roles in decomposition and nutrient cycling processes. We determined how communities of these organisms respond to changes in moisture availability and whether common patterns occur along fine-scale grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
73
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(91 citation statements)
references
References 73 publications
(98 reference statements)
11
73
1
6
Order By: Relevance
“…From semiarid systems, more idiosyncratic patterns emerge, with some nematode genera increasing and others decreasing under drying conditions, also depending on the soil temperature Nagy 2000, Bakonyi et al 2007). A study conducted across mesic, xeric and arid grasslands and a polar desert found that soil nematode numbers decreased with increased moisture availability in each ecosystem except for the arid site, where no relationship was found (Sylvain et al 2014). In a recent meta-analysis Blankinship et al (2011) demonstrated that the effect of precipitation on soil biota abundance was independent of taxon, body size or trophic group, but did depend on ecosystem type; while this effect was positive in boreal forests, coniferous forests and deciduous forests, no effect was observed in grassland, heathland or tundra.…”
Section: Nematode Responses To Long-term Alterations In Water Availabmentioning
confidence: 97%
See 1 more Smart Citation
“…From semiarid systems, more idiosyncratic patterns emerge, with some nematode genera increasing and others decreasing under drying conditions, also depending on the soil temperature Nagy 2000, Bakonyi et al 2007). A study conducted across mesic, xeric and arid grasslands and a polar desert found that soil nematode numbers decreased with increased moisture availability in each ecosystem except for the arid site, where no relationship was found (Sylvain et al 2014). In a recent meta-analysis Blankinship et al (2011) demonstrated that the effect of precipitation on soil biota abundance was independent of taxon, body size or trophic group, but did depend on ecosystem type; while this effect was positive in boreal forests, coniferous forests and deciduous forests, no effect was observed in grassland, heathland or tundra.…”
Section: Nematode Responses To Long-term Alterations In Water Availabmentioning
confidence: 97%
“…The nematode samples were ultimately preserved in 5% formalin solution. The 2009 and 2010 nematode and moisture data from the control, þ80% and À80% treatments have been used together with data from natural gradients in an earlier wider assessment of soil fauna responses to soil moisture availability at different sites and across time (Sylvain et al 2014).…”
Section: Sampling Extraction and Identificationmentioning
confidence: 99%
“…This could be caused by environmental factors, especially soil pH (Zhang et al 2015) or soil moisture (Sylvain et al 2014). Another reason could be the food supply inside the ecosystem and the level of microhabitat transformation (Smrž et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Altered precipitation regimes, including drought, may create thresholds that alter nematofauna community composition. For example, bacterial feeding nematodes exhibit more sensitivity to drought than fungal feeding nematodes and drought conditions have been linked to a significant reduction in nematofauna abundance [12], resulting in altered trophic patterns, thus altered ecosystem functioning [10]. Understanding how water balance impacts soil biological communities and plant production is of paramount importance for future management and sustainability in a context of climate change.…”
Section: Introductionmentioning
confidence: 99%